Study on Prediction Method for Postconstruction Settlement of Loess Fill Foundation in Northern Shaanxi, China - Kui Liu; Kangze Yuan; Boyi Shi (Advances in Civil Engineering)
In order to solve the problem of shortage of construction land in the loess hilly and gully area of northern Shaanxi, the local people usually adopted the method of excavating and filling. The postconstruction settlement was an important index to evaluate the stability of the loess fill foundation. Through laboratory test analysis, the stress-strain and the strain-time relationship of compacted loess were obtained. It showed that the stress-strain curves varied as power functions, and the relationship between strain and time was hyperbolic. Based on the layerwise summation method, a creep equation to predict the postconstruction settlement of loess fill foundation was established. The field monitoring data show that the fitting effect is better. Using this equation, the postconstruction settlement of loess fill foundation with different compaction coefficients and thickness was predicted. Finally, the stability evaluation criteria of loess fill foundation with various thickness and compaction coefficient were proposed. This method provided a new idea to solve the problem of postconstruction settlement of loess fill foundation.